2023
DOI: 10.1002/adma.202306691
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Polymer Nanoparticles with Intrinsic Aqueous Dispersibility for Conductive Hydrogels

Joshua Tropp,
Caralyn P. Collins,
Xinran Xie
et al.

Abstract: Conductive hydrogels are promising materials with mixed ionic‐electronic conduction to interface living tissue (ionic signal transmission) with medical devices (electronic signal transmission). Beyond signal transduction, the hydrogel form factor also uniquely bridges the wet and soft biological environment with the dry and hard environment of electronics. The synthesis of such hydrogels for bioelectronics requires scalable, biocompatible fillers with high electronic conductivity and compatibility with common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…For the live-dead assay, the following procedure was followed [99][100][101][102]: L929 cells, derived from L-connective mouse tissue strain, were obtained from ATCC (Cat no. CCL-1) and seeded onto nerve samples using a dynamic bioreactor, as previously described [103].…”
Section: In Vitro Cell Cytotoxicitymentioning
confidence: 99%
“…For the live-dead assay, the following procedure was followed [99][100][101][102]: L929 cells, derived from L-connective mouse tissue strain, were obtained from ATCC (Cat no. CCL-1) and seeded onto nerve samples using a dynamic bioreactor, as previously described [103].…”
Section: In Vitro Cell Cytotoxicitymentioning
confidence: 99%
“…Given the aforementioned advantages for control of scaffold properties and engineering cell-material interactions, we sought to fabricate scaffolds by 3D printing PEDOT:PSS hydrogels. In the past few years, several methods have been developed for extrusion-based [24][25][26][27][28][29][30][31][32][33][34] or light-based [35][36][37] 3D printing PEDOT:PSS hydrogels. However, the majority of these studies utilize 3D printing for patterning on substrates resulting in 2D conformable electrodes for implantable or wearable applications rather than for 3D in vitro interfacing.…”
Section: Introductionmentioning
confidence: 99%
“…However, photoprinting conductive hydrogels is still a challenging task because the conductive polymer absorbs UV light which may prevent photoactivation and cross-linking. To address this challenge, several studies have reported the fabrication of composite hydrogels of PEDOT:PSS and polyethylene glycol diacrylate (PEGDA) as a photocurable cross-linker using a visible-light photoinitiator system. , The resulting hydrogels are patternable but usually show low electrical conductivity, likely due to low loadings of conductive polymer in an insulating scaffold. Instead, Wei et al recently reported the preparation of 3D-printed conductive hydrogels by photopolymerization of the EDOT monomer .…”
Section: Introductionmentioning
confidence: 99%